Effect of trichostatin a on viability and microRNA expression in human pancreatic cancer cell line BxPC-3 - Zhang, S.; Cai, X.; Huang, F.; Zhong, W.; Yu, Z. (Experimental Oncology, 2008)
Aim: To investigate the influence of trichostatin A (TSA) on inhibition of cell proliferation and induction of apoptosis in human pancreatic cancer cells. Methods: MTT-based cytotoxicity assay was used to evaluate the cell viability after treatment with TSA. Cell cycle distribution and apoptosis were examined by means of flow cytometry. Expression of microRNA was determined with microRNA array. Expression of miR-200c and miR-21 was detected by Northern blotting. Results: TSA significantly inhibited the proliferation of BxPC-3 human pancreatic cancer cells in a time- and dose-dependent manner. BxPC-3 cells treated with TSA were arrested in G0/G1 phase and were characterized by increased apoptotic rate, accompanied by differential expression of microRNAs. Conclusions: The results suggest that TSA may activate expression of microRNAs that may act as tumor suppressor in human pancreatic cancer cell line BxPC-3. Цель: изучить влияние трихостатина A (TSA) на ингибирование пролиферации клеток и индукцию апоптоза в клеточной линии
рака поджелудочной железы человека. Методы: для оценки жизнеспособности клеток после их обработки TSA применяли
основанный на MTT цитотоксический тест. Распределение клеток по фазам клеточного цикла и процент апоптических клеток
определяли с помощью проточной цитофлуориметрии. Экспрессию микроРНК изучали с использованием микроРНК-чипа.
Экспрессия miR-200c и miR-21 исследована с помощью Нозерн-блот анализа. Результаты: TSA значительно ингибировал
пролиферацию клеток линии рака поджелудочной железы человека BxPC-3, и этот процесс зависел от времени инкубации
и концентрации препарата. Клетки BxPC-3, обработанные TSA, были остановлены в G0/G1-фазе клеточного цикла, увеличивалось
количество апоптотических клеток, что сопровождалось изменением экспрессии микроРНК. Выводы: полученные
результаты позволяют предположить, что TSA может активировать экспрессию микроРНК, которые в свою очередь выступают
онкосупрессорами опухоли в клетках линии рака поджелудочной железы BxPC-3.